A tactile twist: decoding the phenomena of mechanical itch and alloknesis - Follansbee, Taylor; Dong, Xinzhong (Frontiers in Molecular Neuroscience, 2023)
Itch is a sensation in the skin which provokes the desire to scratch. In the past few decades there has been a significant elucidation of the immune and neural pathways which underly the sensation of itch. An interesting divergence in the itch pathway relates to the type of stimulation used to evoke an itchy sensation. Commonly, chemical mediators of itch such as histamine are injected into the skin where they activate their cognate receptors on sensory neurons. Another way to evoke itch, particularly in patients with chronic itch, is to use light mechanical stimulation. Investigation into these pathways utilizing the mouse model have shown that the neuronal pathways which underly chemical itch are distinct from those which mediate itch in response to mechanical stimulation. Specific populations of primary sensory neurons, spinal interneurons and transmission neurons have been identified which suggests a labeled line for itch transmission. Additionally, Piezo channels, which underly mechanosensation, were discovered to play an important role in the mechanical itch pathway. Given these novel findings relating to the mechanical itch pathway, the purpose of this review is to summarize the reports from human subjects and animal studies to highlight the advances in our understanding of mechanical itch and alloknesis.